Fitness landscape analysis of convolutional neural network architectures for image classification - Rodrigues, Nuno M. (2022)
Rodrigues, N. M., Malan, K. M., Ochoa, G., Vanneschi, L., & Silva, S. (2022). Fitness landscape analysis of convolutional neural network architectures for image classification. Information Sciences, 609(September), 711-726. https://doi.org/10.1016/j.ins.2022.07.040. ----- Funding: The work of K.M. Malan was supported by the National Research Foundation, South Africa, under Grant 120837. This work was partially supported by FCT, Portugal, through funding of the LASIGE Research Unit (UIDB/00408/2020 and UIDP/00408/2020); projects GADgET (DSAIPA/ DS/ 0022/ 2018), BINDER (PTDC/ CCI-INF/ 29168/ 2017), AICE (DSAIPA/ DS/ 0113/ 2019); Nuno Rodrigues was supported by PhD Grant 2021/05322/BD.